Self–deception and doxastic voluntarism - Fernández Acevedo, Gustavo (Estudios de Filosofía, 2018)
The doctrine known as “doxastic voluntarism”, that is, the idea according to which we can freely adopt our beliefs, has been considered as untenable by most philosophers. Moreover, it is possible to distinguish two versions of this doctrine. The direct doxastic voluntarism corresponding to the latter description; and the indirect doxastic voluntarism, that sustains a more moderate thesis according to which it would be possible to induce certain beliefs in ourselves in an indirect way through the planned modification of our conducts. Bernard Williams, who has presented influential arguments against the direct doxastic voluntarism, has admitted that its indirect variation is possible, but only via self–deception. In this article, different contemporary conceptions of self-deseption are examined, to conclude that under any of these can this phenomenon constitute an efficient means for the indirect voluntary induction of beliefs.